Lost landscapes : LOLA Landscape Architects - Van der Veeken, Cees; Meindertsma, Eelkje; Veenstra, Arianne (Rotterdam : nai010 publishers, 2013)
"Rotterdam landscape architects LOLA (Lost Landscapes) design and study landscapes that are forgotten, derelict or about to change. Since its founding in 2006, the office has worked on conceptual as well as realized projects in the city, on the outskirts and in the countryside. The designers at LOLA combine knowledge of large-scale ecosystems with contemporary ideas about space and nature. (...) Winners of the Rotterdam-Maaskant Prize for Young Architects."--Cover.
Journeymen -- Green revolution -- Sites of contested meaning -- Singelpark Leiden -- Life lines -- From bubbles to bundles -- Delta reanimation -- The long tail of leisure -- Lost landscapes -- Star maze -- The fat of the land -- Re-visioning nature -- New romanticism in the Dutch landscape.
Cover title.
boek
Keywords: LOLA Landscape Architects; Landscape architectural firms -- Netherlands -- Rotterdam; Landscape architecture -- Netherlands